ChemInform Abstract: Mild and Efficient Synthesis of Benzo‐Fused Seven‐ and Eight‐Membered Ring Lactams: A Convenient Approach to Biologically Interesting Chemotypes. Issue 31 (11th July 2013) - Kenwright, Jayne L.; Galloway, Warren R. J. D.; Wortmann, Lars; Spring, David R.
Abstract The title compounds (II) are efficiently obtained via Beckmann rearrangement of cyclic oximes.